The neurosociology of Auguste Comte. (June 2020) - McVeigh, Ryan
This article explores the role of phrenology in the work of Auguste Comte. I begin by reviewing the historical and contemporary significance of this doctrine to show the direct lineage that exists between phrenology and what we now call cognitive neuroscience. I then demonstrate the impact of phrenology on Comte's sociological theory and make the claim that his paradigm exemplifies what TenHouten called 'neurosociology.' Following this, I show how Comte's social epistemology rejected biological reductionism and considered neurophysiology a subfield of sociology. This results in a somewhat startling assertion: Comte saw sociology as a cognitive science. After outlining Comte's original vision for sociology as a discipline, I place Comte's system in critical contact with 21st century neuroscience and suggest fruitful ways to move the neurosociology paradigm forward. In this I demonstrate that Comte's vision for sociology is worth pursuing today, even while the specifics of his doctrine are not.